2021
DOI: 10.4174/astr.2021.100.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term graft patency after lower extremity arterial bypasses

Abstract: Purpose This study was conducted to determine factors associated with long-term graft patency after lower extremity arterial bypass (LEAB). Methods Database of LEABs for patients with chronic arterial occlusive disease (CAOD) at a single institution was retrospectively reviewed. To determine the factors we compared demographic, clinical, and procedural variables between 2 patient groups; group I (graft patency < 2 years) and group II (graft patency ≥ 5 years after LEAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The non-statin group, on the other hand, included more patients with CLI (77 percent vs 57 percent, p<0.001), non-ambulatory status (25. Jung et al, [13] reported that when the patient characteristics of the two groups were examined, group II patients were younger (median, 69 years vs. 66 years; p=0.024) and more hypertensive (60.8 percent vs. 74.6 percent; p=0.017) than group I patients (short-term graft patency). There were more limbs in Group II with claudication as a reason for LEAB (51.2 percent vs. 70.9 percent, p=0.001), but no substantial variations in other comorbidities or blood test findings.…”
Section: Discussionmentioning
confidence: 99%
“…The non-statin group, on the other hand, included more patients with CLI (77 percent vs 57 percent, p<0.001), non-ambulatory status (25. Jung et al, [13] reported that when the patient characteristics of the two groups were examined, group II patients were younger (median, 69 years vs. 66 years; p=0.024) and more hypertensive (60.8 percent vs. 74.6 percent; p=0.017) than group I patients (short-term graft patency). There were more limbs in Group II with claudication as a reason for LEAB (51.2 percent vs. 70.9 percent, p=0.001), but no substantial variations in other comorbidities or blood test findings.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the use of statins was associated with better lesion permeability in patients undergoing infrapopliteal angioplasty and greater amputation-free survival, but did not decrease the rate of amputations ( 123 ). Another very recent study in patients with bypass observed that statin therapy was associated with long-term graft permeability on the univariate analysis, but was no longer an independent factor on the multivariate analysis ( 106 ).…”
Section: Effects Of Statins In Patients Undergoing Revascularization Proceduresmentioning
confidence: 99%